DESCRIPTION OF WORK SAFETY UNDERSTANDING AND AWARENESS IN THE SCIENCE LABORATORY OF JUNIOR HIGH SCHOOL STUDENTS IN INDONESIA - Adhitya Chandra Permana (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
Laboratory guidelines not only provide practical experience to students but also help students to identify hazardous materials and work safety in the laboratory. This study aims to investigate the scientific understanding and the awareness of Indonesian junior high school students about safety signs in the laboratory. The survey questionnaires were given to 191 third-grade junior high school students who had received work safety material in the laboratory. The findings indicated that the majority of students had misconceptions about the definition of hazardous materials in the laboratory. In addition, they experienced low laboratory work safety awareness. In the interview, the researcher found that students did not pay attention to the safety signs on the packaging label of the material during the experiment. The results of this study fill the gap in laboratory learning studies. The research results also provide information to improve the quality of learning in the laboratory, especially in increasing students' awareness of how to use, store, and properly dispose of materials in the laboratory.